USE OF ELEMENTS OF ETHNIC SCIENCE IN THE PROCESS TRAINING OF FUTURE ENGINEERS OF TECHNICAL HIGHER EDUCATION INSTITUTIONS - A.V. Kochubey (Academy of Cognitive and Natural Sciences, 2008)
The revival spiritual and moral is a necessity of time. In clause the conceptual principles of spiritual - moral education of the students by means of national knowledge are proved.